Reliability of the Maximal Lactate Accumulation Rate in Rowers - Held, Steffen; Rappelt, Ludwig; Brockherde, Julia; Donath, Lars (International Journal of Sports Medicine, 2023)
The maximal lactate accumulation rate (VLamax) has been linked to lactic anaerobic performance. Hence, accurate and reliable assessment is crucial in sport-specific performance testing. Thus, between-day reliability data of rowing-specific VLamax assessment was examined. Seventeen trained rowers (eight females and nine males; 19.5±5.2 yrs; 1.76±0.08 m; 70.2±8.9 kg; V̇O2max: 54±13 ml/min/kg) performed 20-s sprint tests on two separate days (one week apart) on a rowing ergometer. VLamax, peak lactate concentration, time to peak lactate, and mean rowing power were measured. Good to excellent intraclass correlation coefficients (ICCs), low standard error of measurement (SEM), and acceptable levels of agreement (LoAs; 90% confidence interval) for VLamax (ICC=0.85; SEM=0.02 mmol/L/s; LoA±0.09 mmol/L/s), peak lactate (ICC=0.88; SEM=0.3 mmol/L; LoA±1.4 mmol/l), time to peak lactate (ICC=0.92; SEM=0.1 min; LoA±0.5 min), and mean rowing power (ICC=0.98; SEM=3 W; LoA±39 W) were observed. In addition, VLamax was highly correlated (r=0.96; p≤0.001) to rowing power. Thus, VLamax and sprint performance parameters can be measured highly reliably using this sport-specific sprint test in rowing.
Keywords: glycolytic rate; exercise testing; lactic anaerobic power; cLamax